Um museu de duas faces: poesia da circunstância em João Cabral de Melo Neto - Edneia Rodrigues Ribeiro (2019)
Starting from the approximation of metapoetry and occasional verse, which are considered the basic characteristics of João Cabral de Melo Neto's book "Museu de tudo" (1975), this dissertation analyses a number of poems that have as their main theme the work of other Brazilian writers, among the author's friends, such as Manuel Bandeira, Vinicius de Moraes, Willy Lewin, Joaquim Cardozo and Marques Rebelo. In spite of the general consensus about occasional poetry as a lesser genre, dependent on improvisation, it must be noted that theoretical approaches of this matter are scarce. Among those who have dealt with the subject, this dissertation emphasizes Pedrag Matvejevitch and João Cabral himself, who made a few remarks about it in his unpublished essay "Brazilian Poetry". The intersection between occasional verse and metalinguistics demonstrates that occasional poetry - although rejected by many, including Cabral - may be also a form of critical poetry.